Ultra-High-Field Magnetic Resonance Spectroscopy in Psychiatry - Godlewska, Beata R.; Clare, Stuart; Cowen, Philip J.; Emir, Uzay E. (Frontiers in Psychiatry, 2017)
The advantages of ultra-high-field (UHF≥7T) MR have been demonstrated in a variety of MR acquisition modalities. Magnetic resonance spectroscopy (MRS) can particularly benefit from substantial gains in signal-to-noise ratio (SNR) and spectral resolution at UHF, enabling the quantification of numerous metabolites including, glutamate, glutamine, glutathione and γ-aminobutyric acid that are relevant to psychiatric disorders. The aim of this review is to give an overview about the advantages and advances of UHF MRS and its application to psychiatric disorders. In order to provide a practical guide for potential applications of MRS at UHF, a literature review is given, surveying advantages and disadvantages of MRS at ultra-high-field (UHF). Key concepts, emerging technologies, practical considerations and applications of UHF MRS are provided. Second, the strength of UHF MRS is demonstrated using some examples of its application in psychiatric disorders.